Imipramine Induces Brain-Derived Neurotrophic Factor mRNA Expression in Cultured Astrocytes - Katsura Takano; Hiroshi Yamasaki; Kenji Kawabe; Mitsuaki Moriyama; Yoichi Nakamura (Elsevier, 2012)
Depression is one of the most prevalent and livelihood-threatening forms of mental illnesses and the neural circuitry underlying depression remains incompletely understood. Recent studies suggest that the neuronal plasticity involved with brain-derived neurotrophic factor (BDNF) plays an important role in the recovery from depression. Some antidepressants are reported to induce BDNF expression in vivo; however, the mechanisms have been considered solely in neurons and not fully elucidated. In the present study, we evaluated the effects of imipramine, a classic tricyclic antidepressant drug, on BDNF expression in cultured rat brain astrocytes. Imipramine dose-dependently increased BDNF mRNA expression in astrocytes. The imipramine-induced BDNF increase was suppressed with inhibitors for protein kinase A (PKA) or MEK/ERK. Moreover, imipramine exposure activated transcription factor cAMP response element binding protein (CREB) in a dose-dependent manner. These results suggested that imipramine induced BDNF expression through CREB activation via PKA and/or ERK pathways. Imipramine treatment in depression might exert antidepressant action through BDNF production from astrocytes, and glial BDNF expression might be a target of developing novel antidepressants. Keywords:: astrocyte, antidepressant drug, brain-derived neurotrophic factor (BDNF), protein kinase A (PKA), cAMP response element binding protein (CREB)